Bastions of Irrational Conservatism? Shop-floor Accounts and the Co-evolution of Organizational and Institutional Change in Russia - Grancelli, Bruno (Organizations and Markets in Emerging Economies, 2012)
On the whole, the co-evolutionary literature on state-business relationships in Russia conveys the idea that significant changes have occurred in property and corporate governance while less change is noticed in management structures, and workplaces are the places less touched by the systemic transformation. This paper critically assesses the idea that organizational changes only proceed from top to down and from the outside to the inside: those who interact in the workplace are not just the receiving end of change. Yet, the cognitive lenses through which this area of empirical reality is seen have often led to the superposition on shop-floor accounts of overarching frameworks such as that of surplus value extraction and the class antagonism it is bound to breed. I argue that better ways to bridge the micro-macro gap may be found within an institutional research that highlights the links between the microlevel of firm capacities for change and the meso level of organizational fields and local socioinstitutional environments. Therefore, the paper reviews some major contributions of the co-evolutionary framework with a focus on the bridging issue of emerging entrepreneurship. Then it addresses the methodological challenge of devising explanatory mechanisms that might improve our understanding of that issue. Two examples are proposed here for a comparative look at the Russian case: the attention for the “strategies of independence” of working people in classic works of industrial sociology as well as for the “social construction of markets” as aggregate outcome of such strategies in the Italian industrial districts. The paper concludes with some remarks on whether a rational model of purposive action is or is not compatible with thick descriptions and high-context explanations of the micro-meso link.